RELATIONSHIP BETWEEN THINK POSITIVE TOWARDS THE OPTIMISM OF PSYCHOLOGY STUDENT LEARNING IN ISLAMIC UNIVERSITY OF RIAU - WILLYTIYO KURNIAWAN (Program Studi Psikologi Islam, 2019)
Optimism learning is learning how to think with more optimistic when we fail to give us a permanent membership to fend off depression. Positive thinking is to make people more optimistic face life and facilitate individuals to move well. The purpose of this study was to determine the relationship between positive thinking towards optimism learning on students of the Faculty of Psychology, Islamic University of Riau. The subjects are fourth and sixth-semester students of Faculty of Psychology, the Islamic University of Riau by the number of subjects 90 students. This study uses quantitative data taken using a scale of positive thinking and optimism scale study. Methods of data analysis using linear correlation with SPSS 18.0 for windows. There was a significant positive relationship between positive thinking towards optimism learning in the fourth and sixth semester students of the Faculty of Psychology, the Islamic University of Riau with correlation coefficient (r) = (0.699) , (p<0.01).